Analysis of Factors Influencing Maternal Intentions in Exclusive Breastfeeding of Infants in The Perinatology - Fauziah, Fika; Setiawati, Nina; Rahmawati, Eni (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: Breast milk is the main source of nutrition in infants 0-6 months. The behavior of the mother in exclusively breastfeeding is influenced by the intentions possessed by the mother, especially in babies in perinatology. Objective: The purpose of this study was to determine the factors that influence the mother's intention in exclusive breastfeeding of infants treated in perinatology. Methods: The method used is cross-sectional with a non-probability sampling technique with total sampling within 1 month of as many as 54 responders. Data analysis using Chi-Square Test and multiple logistic regression. Results: The results showed a significant relationship between maternalknowledge (p = 0.000) and husband support (p = 0.001). Meanwhile, family support (p = 0.114) and nurse support (p = 0.924) were not related to the mother's intention to provideexclusive breastfeeding. The results of multiple logistic regression tests found that the dominant factor that influenced the mother's intention to exclusively breastfeed was husband support (OR=9,754). Conclusion: Husband support is the most dominant factor in influencing the mother's intention to exclusively breastfeed the baby treated in perinatology. Husband support consists of instrumental, informational, judgmental, and emotional support. In this study, the husband was able to provide emotional and instrumental support, for other support still needs to be improved. It is recommended that efforts be made to increase the role of husbands in motivating mothers to provide exclusive breastfeeding, health workers are required to provide health education about the importance of husband's support in providing exclusive breastfeeding.